2016
DOI: 10.1002/aic.15405
|View full text |Cite
|
Sign up to set email alerts
|

Tuning carbon molecular sieves for natural gas separations: A diamine molecular approach

Abstract: This article introduces a new postsynthetic modification method for tuning the separation properties of carbon molecular sieve (CMS) membranes. Polymeric hollow fibers of 6FDA/BPDA‐DAM were pyrolyzed to 550°C under inert Argon, and were then exposed to a tetrahydrofuran solution containing PPM levels of paraphenylenediamine dopant. The original goal of the treatment was to modify the morphology in a manner to prevent relaxation of the CMS to suppress physical aging, envisioned to be analogous to that in glassy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The asymmetric hollow fiber spinning was done by a dry‐jet/wet‐quench spinning process using water as a quench bath coagulant. Spun fibers underwent solvent exchange in water for 3 days, followed by methanol and hexane exchange for 1 h each, and then drying in vacuum oven at 130 °C for 3 h. The details of polymer dope composition, the schematic of hollow fiber spinning setup, and Torlon hollow fiber formation have been described in previously . The Torlon hollow fibers used in this study had a length of 5 cm with inner and outer diameters of 300 and 700 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The asymmetric hollow fiber spinning was done by a dry‐jet/wet‐quench spinning process using water as a quench bath coagulant. Spun fibers underwent solvent exchange in water for 3 days, followed by methanol and hexane exchange for 1 h each, and then drying in vacuum oven at 130 °C for 3 h. The details of polymer dope composition, the schematic of hollow fiber spinning setup, and Torlon hollow fiber formation have been described in previously . The Torlon hollow fibers used in this study had a length of 5 cm with inner and outer diameters of 300 and 700 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hollow fibers have been shown to be excellent gas–solid contactors for various adsorption‐ and membrane‐based separation processes, mainly due to their unique combination of large surface area and high porosity within a packed volume . While polymeric hollow fibers provide numerous advantages for incorporating inorganic compounds and synthesis of composite materials, they suffer from chemical instability and swelling under various MOF hydrothermal synthesis conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has been suggested that these sp 2 -hybridized carbon sheets align into lamellar-like structures, yielding ordered microporous structures. 20 Specifically, these CMS phases display open micropores connected by rigid slit-like ultramicropores to provide high sorption and diffusion coefficients.…”
Section: Carbon Molecular Sieve Membranes For N 2 /Ch 4 Separationmentioning
confidence: 99%
“…20 It has been suggested that these sp 2 -hybridized carbon sheets align into lamellar-like structures, yielding ordered microporous structures. 20 Specifically, these CMS phases display open micropores connected by rigid slit-like ultramicropores to provide high sorption and diffusion coefficients. 21 Different from the well-defined microporous structures which characterize zeolites and metal organic frameworks, CMS exhibit distributions of micropores and ultramicropores.…”
Section: Carbon Molecular Sieve Membranes For N 2 /Ch 4 Separationmentioning
confidence: 99%